Propuesta didáctica alternativa para la resolución de ecuaciones de primer grado utilizando la balanza algebraica virtual con los estudiantes de décimo nivel de la unidad Educativa once de noviembre, Riobamba, Chimborazo 2022 - Cando Cando, Armando Celso (2023)
ABSTRACT: In the teaching of first-degree equations, difficulties and confusions have been found at the moment in which the mathematical contents pass from arithmetic to algebra, for this reason the objective of this work is to elaborate a proposal for the use of the virtual algebraic balance with GeoGebra for learning first degree equations with an unknown in the tenth degree. A quantitative approach has been used, with a non-experimental, descriptive and applied design. The sample was made up of the students who attended the tenth parallel year F in the "Once De Noviembre" Educational Unit during the 2021-2022 school period. The survey and the test were developed as a technique and two questionnaires as instruments, one intended to obtain information on the difficulties that the students had and another to establish the procedural errors in learning the subject of first-degree equations with an unknown. Among the main conclusions, it is established that approximately 70% have difficulties in the correct application of mathematical processes, identifying errors such as: poor recognition of variables, incorrect clearance of unknowns, difficulties in the transformation of mathematical language into natural language and vice versa, as well as the ignorance of the axioms or laws that are used to carry out each one of the steps in the resolution. The proposal based on the ERCA methodology was prepared and incorporated elements of ethnomathematics and for its dissemination a product was made in a digital periodical format.